Sufficient protection for Australian children rights? Beyond the Corbett Bill : a comparative analysis of attitudes and legal responses to corporal punishment in the home - Milfull, Cathy (Discussion paper (National Children's and Youth Law Centre (Australia)) ;, 2000)
The Crimes Amendment Child Protection - Excessive Punishment Bill 2000 seeks to claryfy the law regarding corporal punishment of children. Addresses the right to the private autonomy of the family and the right to cultural self-determination and the level of physical punishment appropriate to be used against children.